Antike Malerei zwischen Lokalstil und Zeitstil, Tafelband Akten des XI. Internationalen Kolloquiums der AIPMA , 13.-17. September 2010 in Ephesos - Zimmermann, Norbert (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
Under the main theme "Ancient Painting between Local Style and Period Style", 150 specialists from 16 nations dedicated themselves in September 2010 in Ephesus to the characteristics of period and/or local styles in ancient painting and to the relationship and influence of local styles and traditions. The publication at hand presents the 45 lectures regarding the general topic as well as 17 further contributions on novitates and 40 posters.